2004
DOI: 10.1128/jvi.78.12.6313-6321.2004
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of the Catalytic Subunit of DNA-Dependent Protein Kinase during Poliovirus Infection

Abstract: DNA-dependent protein kinase (DNA-PK) is a serine/threonine kinase that has critical roles in DNA double-strand break repair, as well as B-and T-cell antigen receptor rearrangement. The DNA-PK enzyme consists of the Ku regulatory subunit and a 450-kDa catalytic subunit termed DNA-PK CS . Both of these subunits are autoantigens associated with connective tissue diseases such as systemic lupus erythematosus (SLE) and scleroderma. In this report, we show that DNA-PK CS is cleaved during poliovirus infection of He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The ability of rhinovirus 2A pro to cleave mitochondrial antiviral-signalling protein (mAVS; also known as VISA, CARDIF and IPS1), an intermediate in the interferon generation pathway, might contribute to the insensitivity of these viruses to interferons 71 . 2A pro also cleaves the catalytic subunit of DNA-dependent protein kinase, which, among other activities, is involved in the induction of pro-inflammatory cytokines 72 . Cardiovirus L also suppresses interferon production by affecting the activation of interferon regulatory factor 3, but the exact mechanism of this interference has not yet been identified 32,50,73,74 .…”
Section: Effects On Innate Immunity and Viral Pathogenicitymentioning
confidence: 99%
“…The ability of rhinovirus 2A pro to cleave mitochondrial antiviral-signalling protein (mAVS; also known as VISA, CARDIF and IPS1), an intermediate in the interferon generation pathway, might contribute to the insensitivity of these viruses to interferons 71 . 2A pro also cleaves the catalytic subunit of DNA-dependent protein kinase, which, among other activities, is involved in the induction of pro-inflammatory cytokines 72 . Cardiovirus L also suppresses interferon production by affecting the activation of interferon regulatory factor 3, but the exact mechanism of this interference has not yet been identified 32,50,73,74 .…”
Section: Effects On Innate Immunity and Viral Pathogenicitymentioning
confidence: 99%
“…All of these 2A-induced events serve to enhance viral protein synthesis. In addition, poliovirus infection or 2A expression in HeLa cells causes alterations in the nuclear pore structure resulting from cleavage of specific components of the nuclear pore complex (8,15,33). These alterations produce bidirectional increases in permeability of the nuclear envelope, which permit redistribution of cellular proteins that normally reside in the nucleus to the cytoplasm, where they are available for viral translation or other replication reactions.…”
mentioning
confidence: 99%
“…These include histone H3, a substrate for a foot-and-mouth disease virus protease [36], as well as the La antigen, which is cleaved by the poliovirus 3C protease [37]. Recently, we have shown that DNA-PK CS is cleaved by a picornavirus 2A protease [38], indicating that viral proteases may contribute to the generation of novel autoantigenic epitopes. Morecomprehensive screens may identify additional substrates for viral proteases.…”
Section: Viral Proteasesmentioning
confidence: 99%